Information And Communications Technology (ICT) In Initial Teacher Education: What Can Turkey Learn From Range Of International Perspectives? - ALTUN, Taner (Journal of Turkish Science Education, 2007)
This study aims to review the strategies of preparing pre-service teachers to use new technologies to enhance subject matter training in teacher education (ITE) programs in variouscontexts, and intends to come out with the some possible ways of pedagogically appropriate integration of Information and Communications Technology (ICT) into Turkish ITE programs.Through the literature review, perspectives from German, British, American, Japanese and Turkish ITE programs are examined in terms of the diffusion of ICT and as a result general strategies ofintegrating ICT into the ITE programs are articulated. Literature suggests that there are four essential factors which need to be taken in to consideration when ICT is intended to beimplemented into ITE. These vital factors are; ICT infrastructure and physical resources, curriculum and policy development, training lecturers and pedagogical training of teachers in ICT.At the end of the paper, a critical analysis about pedagogically appropriate integration of ICT into ITE programs is made.
Keywords: Initial Teacher Education; Information and Communications Technology; Pedagogy